The fantasy of reunion: the rise and fall of the Association for the Promotion of the Unity of Christendom - Chapman, M (Cambridge University Press, 2007)
This paper traces the history of the Association for the Promotion of the Unity of Christendom, one of the most successful of the eccentric and idiosyncratic private ecumenical initiatives of the mid-nineteenth century. The principal motivation behind the venture was a Romantic medievalism inspired by the lay Roman Catholic Ambrose Phillips de Lisle and the Anglican ritualistic priest, Frederick George Lee. While initially attracting widespread support, the leaders failed to recognise the power of vested interests in both Churches. After a vigorous denunciation by Henry Manning, the hopes of reunion proved to be little more than a dream.